Measurement of electron beam energy characteristics at an industrial accelerator - Pomatsalyuk, R.I.; Shevchenko, V.A.; Shlyakhov, I.N.; Tenishev, A.Eh.; Titov, V.Yu.; Titov, D.V.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2017)
At an electron accelerator, the particle energy is one of critical parameters in the technological processes, as well as when conducting the radiation tests. The report presents the results of modernization of beam energy-spectrum analyzer on the basis of a 90˚ electromagnet of an industrial Linac LU-10 (10 MeV, 10 kW). A control system on the basis of a multifunction USB device for the analyzer data acquisition and processing has been developed. The results of measuring the energy characteristics of the accelerator beam with the analyzer, as well as using a dosimetric wedge technique are presented. A computer simulation method was used to study the features of the wedge application in case of a beam with wide spectrum. The conditions of on-line electron energy control using a wide-aperture stack monitor are investigated. A comparative analysis of results of the energy determination by the different techniques is carried out.